Gratification of Public Officials Reviewed in Perspective Islamic Law - Faisol, Faisol; Khusniyah, Nurul Khotimatul; Sahri, Mat (STAINI Press, 2023)
This research aims to describe the gratification practices accepted by public officials within the framework of an Islamic legal perspective. The research method used is a literature review study, where various literature sources such as academic journals, books, articles and related papers are studied comprehensively. The results of this research show, among other things. First, Islamic law has a firm view on the practice of gratification accepted by public officials. This practice is considered to violate the principles of justice, transparency and accountability which are the basis of Islamic teachings. Second, in the view of Islamic law, accepting gratuities by public officials can be considered a form of bribery or rasywah which damages the morality and integrity of individuals and society as a whole. Third, Islamic scholars and scholars throughout history have voiced their rejection of the practice of gratification in the context of government or public officials